Physiotherapy Management for Tennis Elbow: A Case Study - Nazihah, Zulvy; Zakaria, Ricky Fauzi; Perdana, Suryo Saputra (Universitas Muhammadiyah Surakarta, 2022)
Introduction: In daily life, people with activities or work that involves repetitive hand movements can lead to complaints in the arms, especially the elbows, one of the risk factors for tennis elbow. Tennis elbow is a disorder involving joint mobility and range of motion, muscle performance associated with tendonosis inflammation of the wrist extensor tendon attached to the lateral epicondyle that can cause pain and disability. Tennis elbow happens in about 40% of the population and mainly occurs in men and women aged 35 to 54. In addition, 50% of tennis players also experience pain in the elbow, with 75-80% due to tennis elbow. The physiotherapy modalities used are SWD (Short Wave Diathermy) and exercise therapy in the form of active and strengthening exercises.Case Presentation: A 40-year-old woman works as a private employee in print media in Yogyakarta with pain in her right elbow. The pain has been felt since September 2021, after the patient painted his house. Currently, the pain is felt during daily activities such as personal hygiene, carrying loads, riding a motorcycle, and typing in the office.Management and Outcome: The patient undergoes three physiotherapy treatments, 60 minutes for each session, in the form of TENS, SWD, and exercise therapy. The evaluation consists of pain measurement using NRS, muscle strength measurement using MMT, Range of Motion measurement using a goniometer, and functional ability measurement using PRTEE.Discussion: The aim of the physiotherapy program for tennis elbow patients is to reduce pain andimprove muscle strength, joint range of motion, and functional ability. The exercise therapy was also performed on tennis elbow patients, which was aimed to help the muscles contract and relax to control specific movements.Conclusion: Physiotherapy program in the form of TENS, Short Wave Diathermy, and Exercise therapy for patient with diagnosed tennis elbow gave several improvements such as decreasing pain, increasing range of motion, muscle strength, and functional ability.